CYP2D6 UM phenotype is not related to suicide attempts in depressive patients in secondary psychiatric care - Asp, Marie; Holck, Amanda; Green, Henrik; Westrin, Åsa; Reis, Margareta (Nordic Journal of Psychiatry, 2025)
Introduction: The hepatic cytochrome P450 system includes the polymorphic CYP2D6 gene. CYP2D6 ultra rapid metabolizers (UMs) were 10-fold more common in suicide victims than in the general population in a previous study. The aim of this study was to investigate if the occurrence of the CYP2D6 UM genotype differs between subjects with and without previous suicide attempt in patients treated for depression in secondary psychiatric care. Material and methods: The study “Genes, Depression and Suicidality” (GEN-DS) included 407 subjects treated for depression in secondary psychiatric care between 2012 and 2021. Subjects were genotyped for CYP2D6, interviewed according to a semi-structured protocol and diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders 4th ed (DSM-IV-TR). Results: Of the 407 subjects, 128 subjects (31.4%) had a history of one or more suicide attempt. Two (1.6%) in the suicide attempt group were categorized as UMs, as compared to 9 (3.2%) in the non-suicide attempt group. There was no statistical significance between the groups (p = 0.27, Fisher’s exact test). Bipolar disorder, personality disorders, substance use disorders and lifetime presence of psychotic symptoms were more common in suicide attempters. Conclusion: Based on our results, CYP2D6 UMs are not over-represented among suicide attempters in depressed patients treated in secondary psychiatric care. Analysis of CYP2D6 genotype can be useful for optimizing pharmacological treatment in depression but genotyping does not seem relevant for the clinical assessment of suicidality in difficult-to-treat depression.
Keywords: CYP2D6 phenotypes; depression; psychiatric comorbidity; suicidality; suicide attempt